An Empirical Examination of IPO Underpricing: Evidence from China - Shao, pengfei (2017)
Much evidence suggests that the underpricing of initial public offerings is a common phenomenon in the stock markets of various countries. IPO underpricing reflects the efficiency of capital markets. Previous studies reported the level of IPO underpricing in Chinese A-share market is much higher than the average level of 60% in the emerging markets (Jenkinson and Ljungqvist, 2001). In this paper, the degree of IPO underpricing in Chinese stock market and its determinants are studied by empirical analysis. Using data in Shanghai and Shenzhen stock exchange from January 2008 to December 2016, this paper studied three main factors of Chinese underpriced IPOs, which are information asymmetry, reputation of underwriters and ownership structure. Our results showed that although the level of Chinese IPO underpricing is still higher, the reform of issuance mechanism leads Chinese underpricing level to bring down to emerging market level. Information asymmetry is the main reason for underpriced IPOs. Besides, the underwriters’ reputation and ownership structure have effects on the allocation of IPOs.